Existence of solutions for a perturbed p-Laplacian system with critical exponent in. Issue 11 (18th August 2017) - Li, Qin; Yang, Zuodong
Abstract : In this paper, we consider the following perturbed p -Laplacian system where, , satisfy, denotes the critical Sobolev exponent. Under some mild conditions on V, g and h, we show that the problem has at least one positive weak solution provided, where is a sufficiently small positive number. Moreover, in X as